2022
DOI: 10.3390/biology11111683
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome and Female Health

Abstract: The possession of two X chromosomes may come with the risk of various illnesses, females are more likely to be affected by osteoarthritis, heart disease, and anxiety. Given the reported correlations between gut microbiome dysbiosis and various illnesses, the female gut microbiome is worthy of exploration. Herein, we discuss the composition of the female gut microbiota and its dysbiosis in pathologies affecting the female population. Using PubMed, we performed a literature search, using key terms, namely: “gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 109 publications
0
17
0
1
Order By: Relevance
“…We also found that Bacteroides increased significantly in women. Specifically, the abundance of Bacteroides is responsible for the deconjugation of conjugated bile acids synthesized in the liver (Siddiqui et al, 2022 ). Bacteroides vulgatus was significantly higher in women with polycystic ovary syndrome compared with controls (Qi et al, 2019 ; Siddiqui et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that Bacteroides increased significantly in women. Specifically, the abundance of Bacteroides is responsible for the deconjugation of conjugated bile acids synthesized in the liver (Siddiqui et al, 2022 ). Bacteroides vulgatus was significantly higher in women with polycystic ovary syndrome compared with controls (Qi et al, 2019 ; Siddiqui et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the abundance of Bacteroides is responsible for the deconjugation of conjugated bile acids synthesized in the liver (Siddiqui et al, 2022 ). Bacteroides vulgatus was significantly higher in women with polycystic ovary syndrome compared with controls (Qi et al, 2019 ; Siddiqui et al, 2022 ). We inferred that the TLEA female patients had disordered intestinal flora structures and increased Bacteroides compensatively.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may reflect factors such as previous neoadjuvant treatments and antibiotic use, which can significantly impact microbiota and, thus, confound results. Another review published in 2022 reported conflicting results in post-menopausal women regarding the strains of bacteria that were increased or decreased in these groups [ 130 ]. A more in-depth 2022 study showed that the microbial composition of normal adipose breast tissue in breast cancer patients differed, and specific breast bacterial profiles were associated with tumor characteristics [ 131 ].…”
Section: The Complex Interplay Between Menopause Microbiome and Breas...mentioning
confidence: 99%
“…Research on gynecological diseases has shown signi cantly reduced relative abundance of Lachnospiraceae in patients with polycystic ovary syndrome(PCOS) [28]. Siddiqui et al found a decreased quantity of Lachnospiraceae in CC patients [29], while another study demonstrated a positive correlation between Lachnospiraceae and persistent HPV infection in CC, and a negative correlation with HPV clearance [30]. Lachnospiraceae is also associated with the risk of BC, as BC patients have lower relative abundance of Lachnospiraceae compared to the control group [31].…”
Section: Disscussionmentioning
confidence: 99%